Development of rigid side-chain poly(ether sulfone)s based anion exchange membrane with multiple annular quaternary ammonium ion groups for fuel cells. (3rd June 2022) - Du, Shenghua; Li, Songsong; Xie, Ning; Xu, Yaoyao; Weng, Qiang; Ning, Xingming; Chen, Pei; Chen, Xinbing; An, Zhongwei
Abstract: A variety of poly (ether sulfone)s based anion exchange membranes (AEMs) rPES(x/y)-Q with high-density heterocyclic quaternary ammonium groups is prepared by a polycondensation of novel difluoro monomer with biphenol and bis(4-fluorophenyl) sulfone. The AEMs rPES(x/y)-Q exhibit low IEC values in the range of 0.82–1.33 mequiv. g −1 but relatively high hydroxide conductivity of 54.1–82.3 mS cm −1 at 80 °C. Moreover, the AEMs rPES(x/y)-Q display affordable water uptake and good stability due to their rigid side-chain, high-density and stable heterocyclic quaternary ammonium cations. Noticeably, the rPES(5/20)-MPy based single fuel cell displays a large maximum power density of 141 mW cm −2, which reveals a potential application in anion exchange membrane fuel cell. Graphical abstract: Image 1 Highlights: The monomer DFTED with high-density ionziable methyl was synthesized. The AEMs with rigid side-chain and high-density heterocyclic quaternary ammoniums were prepared using the monomer DFTED. The AEMs rPES(x/y)-Q exhibit low IEC values but relatively high hydroxide conductivities and good stabilities. The rPES(5/20)-MPy based fuel cell shows a large maximum power density of 141 mW cm -2, revealing good potential application.